Odisha tribal family health survey: methods, tools, and protocols for a comprehensive health assessment survey - Kshatri, Jaya Singh; Mansingh, Asit; Kavitha, A. K.; Bhattacharya, Haimanti; Bhuyan, Dinesh; Bhattacharya, Debdutta; Rehman, Tanveer; Swain, Aparajita; Mishra, Debashis; Tripathy, Indramani; Mohapatra, Manas R.; Nayak, Moushumi; et al. (Frontiers in Public Health, 2023)
Tribal or indigenous communities have unique health behaviors, challenges, and inequities that nationally representative surveys cannot document. Odisha has one of India's largest and most diverse tribal populations, constituting more than a fifth of the state. State and tribe-specific health data generation is recommended in India's national roadmap of tribal health. The Odisha Tribal Family Health Survey (OTFHS) aims to describe and compare the health status of tribal communities in the state of Odisha and to estimate the prevalence of key maternal-child health indicators and chronic diseases.This paper summarizes the methodology, protocols, and tools used in this survey.This is a population-based cross-sectional survey with a multistage random sampling design in 13 districts of Odisha,India.We will include participants of all age groups and gender who belong to tribal communities.The sample size was calculated for each tribe and aggregated to 40,921, which will be collected from 10230 households spread over 341 clusters.The survey data will be collected electronically in modules consisting of Village, Household, and Individual level questionnaires.The age-group-specific questionnaires were adapted from other national family health surveys with added constructs related to specific health issues of tribal communities, including-critical indicators related to infectious and non-communicable diseases, multimorbidity, nutrition, healthcare-seeking behavior,self-rated health, psycho-social status, maternal and child health and geriatric health.A battery of laboratory investigations will be conducted at the household level and the central laboratory.The tests include liver function tests, kidney function tests, lipid profile, iron profile, and seroprevalence of scrub typhus and hepatitis infections.The datasets from household questionnaires,field measurements and tests and laboratory reports will be connected using a common unique ID in the database management system built for this survey.Robust quality control measures have been built into each step of the survey. The study examines the data focused on different aspects of family health, including reproductive health, adolescent and child health,gender issues in the family, ageing, mental health, and other social problems in a family.Multistage random sampling has been used in the study to enable comparison between tribes.The anthropometric measurements and biochemical tests would help to identify the indicators of chronic diseases among various age groups of the population.